Is a chest radiograph indicated after chest tube removal in trauma patients? A systematic review. Issue 2 (August 2021) - Sweet, Arthur A.R.; Beks, Reinier B.; de Jong, Mirjam B.; van Baal, Mark C.P.M.; IJpma, Frank F.A.; Hietbrink, Falco; Beeres, Frank J.P.; Leenen, Luke P.H.; Groenwold, Rolf H.H.; Houwert, Roderick M.
Abstract : PURPOSE: The aim of this systematic review was to assess the necessity of routine chest radiographs after chest tube removal in ventilated and nonventilated trauma patients. METHODS: A systematic literature search was conducted in MEDLINE, Embase, CENTRAL, and CINAHL on May 15, 2020. Quality assessment was performed using the Methodological Index for Nonrandomized Studies criteria. Primary outcome measures were abnormalities on postremoval chest radiograph (e.g., recurrence of a pneumothorax, hemothorax, pleural effusion) and reintervention after chest tube removal. Secondary outcome measures were emergence of new clinical symptoms or vital signs after chest tube removal. RESULTS: Fourteen studies were included, consisting of seven studies on nonventilated patients and seven studies on combined cohorts of ventilated and nonventilated patients, all together containing 1, 855 patients. Nonventilated patients had abnormalities on postremoval chest radiograph in 10% (range across studies, 0–38%) of all chest tubes and 24% (range, 0–78%) of those underwent reintervention. In the studies that reported on clinical symptoms after chest tube removal, all patients who underwent reintervention also had symptoms of recurrent pathology. Combined cohorts of ventilated and nonventilated patients had abnormalities on postremoval chest radiograph in 20% (range, 6–49%) of all chest tubes and 45% (range, 8–63%) of those underwent reintervention. CONCLUSION: In nonventilated patients, one in ten developed recurrent pathology after chest tube removal and almost a quarter of them underwent reintervention. In two studies that reported on clinical symptoms, all reinterventions were performed in patients with symptoms of recurrent pathology. In these two studies, omission of routine postremoval chest radiograph seemed safe. However, current literature remains insufficient to draw definitive conclusions on this matter, and future studies are needed. LEVEL OF EVIDENCE: Systematic review study, level IV. Abstract : Supplemental digital content is available in the text.